Development of Complementary Operation Plan for Wind Power Fluctuation based on Small-Scale ESS - Jung, Seungmin; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: Various small scale power systems have considered renewable energy as core generating capacity; it has lead a requirement about certain storage capacity to impose flexibility into whole generation management process.Methods/Statistical analysis: It is important to determine a reasonable energy capacity because the device have many controversial cost issues. Therefore, surplus power focused operation plan for storage device was analyzed.Findings: For developing a stable combined system with a number of distributed resources including storage device, an appropriate storage operation plan must be configured based on the system components and changeable condition to handle the internal network appropriately. In this paper, a curtailment-supporting algorithm based on storage device is introduced, and applied in the capacity calculation method. The main purpose is designing basic standard for small-scaled power grid.Improvements/Applications: Several fluctuating conditions are utilized in simulation to reflect critical situation. The analyzing process focuses on the control feasibility with applied capacity and control method.Â Â
Keywords: ESS application; curtailment; microgrid; capacity calculation; EMS